THE ROLE OF ANDROGENS IN OSTEOPOROSIS - Azizova , P.Kh.; Tursunova, Z. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Osteoporosis in men is one of the most important medical and social problems. According to statistics, disability and death due to osteoporosis are 2 times higher in men than in women. But the problem of mineral disorders in men seems to remain somewhat secondary. Molecular mechanisms of changes in the bone system and the factors that affect them should be learned in detail, it is important to manage disorders of the bone system and to prevent them. Materials. Databases were searched until February 23, 2019. A total of 34 articles were analysed including clinical trials and biological experiments. A planned meta-analysis was not possible because of heterogeneity and incomplete reporting of findings. Conclusion. Bone remodeling consists of interrelated stages such as resorption and formation, in which osteoblasts, osteoclasts, and osteocytes together with immune cells and local cytokines participate. Beginning of remodeling begins once osteocytes receive physical load signals or due to endogenous factors (decreased calcium in the blood) due to parathormones. In this case, osteoclastogenesis is stimulated by osteocytes or osteoblasts. The continuous succession of resorption and formation processes, and bone formation in the resorbed amount, is carried out under the influence of stimulating factors such as colony-stimulating factor (KSF ), activating ligand of NF-k receptor (RANKL), and inhibiting factors such as osteoprotegerin (OPG). The differentiation of osteoblasts increases under the influence of androgens, and androgens in physiological concentrations have the property of reducing the amount of PGE, whose synthesis is increased under the influence of IL-6 and parathormone.